2020
DOI: 10.3390/diagnostics10040207
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine/Tryptophan Ratio Predicts Angiotensin Receptor Blocker Responsiveness in Patients with Diabetic Kidney Disease

Abstract: Albuminuria is a measurement and determinant factor for diabetic kidney disease (DKD). Angiotensin receptor blocker (ARB) is recommended for albuminuria in DKD with variable response. To find surrogate markers to predict the therapeutic effect of ARB, we carried out a prospective study to correlate plasma metabolites and the progression of renal function/albuminuria in DKD patients. A total of 56 type 2 diabetic patients with various stages of chronic kidney disease and albuminuria were recruited. ARB was pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Two cross-sectional studies showed that plasma KYN, KYNA, QUIN [61], and KYN/TRP [62] were increased in patients with diabetic kidney disease (DKD) and correlated with eGFR. Four other observational studies found that KYN levels were positively associated with proteinuria [63, 64] and could distinguish between DKD patients with macroalbuminuria and diabetic patients without albuminuria [65, 66]. A small longitudinal study showed that urinary KYNA could differentiate between progressive albuminuria and non-progressive albuminuria in patients with type 1 diabetes [67].…”
Section: Kp In Ckdmentioning
confidence: 99%
“…Two cross-sectional studies showed that plasma KYN, KYNA, QUIN [61], and KYN/TRP [62] were increased in patients with diabetic kidney disease (DKD) and correlated with eGFR. Four other observational studies found that KYN levels were positively associated with proteinuria [63, 64] and could distinguish between DKD patients with macroalbuminuria and diabetic patients without albuminuria [65, 66]. A small longitudinal study showed that urinary KYNA could differentiate between progressive albuminuria and non-progressive albuminuria in patients with type 1 diabetes [67].…”
Section: Kp In Ckdmentioning
confidence: 99%
“…Neither TNF-α nor IL-6 are related to the KYN/Trp ratio, but TNF-α is associated with the KYN level, indicating inflammatory system activation in diabetic nephropathy. Although Trp and the KYN/Trp ratio were shown to be associated with albuminuria, only the KYN/Trp ratio has been proven to predict response to drugs lowering albuminuria levels in diabetic kidney disease [ 45 ].…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…Additionally, the relationship between KYN and albuminuria, proteinuria and GFR diminished in patients taking these drugs, suggesting their beneficial role in kidney function preservation. The plasma KYN/Trp ratio is also reported to be significantly associated with albuminuria and ARB responsiveness in diabetic kidney disease patients [ 45 ].…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…Tryptophan metabolites are uremic solutes and are AHR ligands, which promote CKD progression ( Table 1 ). In a small study of CKD patients, an increased ratio of the tryptophan metabolite, kynurenine, to tryptophan was associated with macroalbuminuria and responsiveness to AT 1 R blockers (ARBs) ( Wu et al, 2020 ). This study suggests upregulation of the ACE/Ang II/AT 1 R pathway in these individuals.…”
Section: Raas and Ahrmentioning
confidence: 99%